ANALISIS TRANSPOR SEDIMEN SUNGAI OPAK DENGAN MENGGUNAKAN PROGRAM HEC-RAS 4.1.0 - Wardhana, Pradipta Nandi (Teknisia, 2015)
Opak river flows in Daerah Istimewa Yogyakarta, Indonesia. The river flow contains sediment material because Opak River’s upstream is at Mount Merapi. The sediment material can settle at river cross section. Deposit of sediment material can reduce cross section discharge capacity. HEC RAS 4.1.0 is developed by U.S Army Corps of Engineering Hydraulics Engineering Centre (USACE). The program have capability to simulate one dimensional flow such as steady flow, unsteady flow, sediment transports, and water quality in natural or artificial network. Based on transport sediment simulation as long as 365 days, sediment material deposition at upstream reach of Opak River is 515,519 tons, middle reach of Opak River is 79,282 tons, and downstream reach of Opak River is 47,300 tons. Meanwhile, there is sediment material deficit at Winongo River as much as 36,231 tons and sediment material deficit at Oyo river as much as 29,437 tons. At the most downstream cross section of Opak River, the cross section change is not significant.